Implementation Of MVC Model In Web-Based Online Ticket Ordering For Magic Art 3d Museum - Putra, Rendi Aditya; Bahri, Syamsul; wahyudin, wahyudin (JURNAL TEKNIK KOMPUTER AMIK BSI, 2025)
The 3D Magic Art Museum is located in the old town. This museum is currently the best museum destination in the old city. This museum displays many interesting paintings and three-dimensional works of art and provides new experiences for visitors. Because previously ticket reservations were made conventionally so tourists had to come directly to the location or use the telephone, so agents were overwhelmed in processing ticket orders. Most visitors who want to pay for tickets still use cash and do not use mobile banking services, which often results in quite long and very inefficient queues, as well as the large number of visitors to the 3D Magic Art Museum, allegedly due to a mismatch between ticket orders and the number of guests in the group. . This research aims to help tourists book tickets more easily and efficiently. At the application design stage, the Model-View-Controller (MVC) method was used. Meanwhile, the programming technology uses the CodeIgniter framework. Therefore, this system can provide a website for museums so that it can be used as a means of ordering and paying online (Payment Gateway), as well as increasing visitor satisfaction through the functionality of this website.